1988
DOI: 10.1128/jb.170.3.1103-1115.1988
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and structural analysis of light-harvesting mutants of Rhodobacter sphaeroides

Abstract: Two mutants of Rhodobacter sphaeroides defective in formation of light-harvesting spectral complexes were examined in detail. Mutant RS103 lacked the B875 spectral complex despite the fact that substantial levels of the B875-oa polypeptide (and presumably the ,( polypeptide) were present. The B800-850 spectral complex was derepressed in RS103, even at high light intensities, and the growth rate was near normal at high light intensity but decreased relative to the wild type as the light intensity used for growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
73
2

Year Published

1989
1989
2010
2010

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 47 publications
3
73
2
Order By: Relevance
“…The purified B800-850 complex in R. sphaeroides was found (23) not to be associated with a third polypeptide as observed for the purified B800-850 complex from Rhodobacter capsulatus (15). However, the polypeptide designated 15A, purified from the ICM of R. sphaeroides (6,7), is always absent in B800-850-strains of R. sphaeroides.…”
mentioning
confidence: 87%
See 3 more Smart Citations
“…The purified B800-850 complex in R. sphaeroides was found (23) not to be associated with a third polypeptide as observed for the purified B800-850 complex from Rhodobacter capsulatus (15). However, the polypeptide designated 15A, purified from the ICM of R. sphaeroides (6,7), is always absent in B800-850-strains of R. sphaeroides.…”
mentioning
confidence: 87%
“…Since PUC-Pv showed no detectable B800-850 complexes under photoheterotrophic growth conditions despite the presence of the 0.5-kb pucBA-specific transcript (Fig. 9, lane 1), the possibility is raised that the polypeptides which comprise the B800-850 complex are synthesized but remain unassembled as we have shown for the B875 complex (9,23). Therefore, the presence of the B800-850-, polypeptide in PUC-Pv was examined by Western immunoblot analysis with antibody specific for the e polypeptide, designated 15B (6,7,23).…”
Section: B800-850 Complexmentioning
confidence: 99%
See 2 more Smart Citations
“…Rb. sphaeroides mutants lacking LH 2 have been shown by the Niederman group (Hunter et al 1988) and in Sam Kaplan's laboratory (Kiley et al 1988) to form tubular rather than vesicular ICM, suggesting that LH 2 has a role in ICM morphogenesis. Kaplan et al (1983) have also shown that phospholipids, synthesized in the CM, are transferred to the ICM by an apparent phospholipid transfer protein at the time of cell division, while proteins and pigments are inserted into CM and ICM throughout the cell cycle.…”
Section: Molecular Aspects Of Membrane Biosynthesismentioning
confidence: 99%